Sex and Age Differences in Patient-Reported Acute Stroke Symptoms - Eddelien, Heidi S.; Butt, Jawad H.; Christensen, Thomas; Danielsen, Anne K.; Kruuse, Christina (Frontiers in Neurology, 2022)
Background: Identification of sex and age difference in presentation of atypical symptoms at stroke onset may reduce prehospital delay and improve stroke treatment if acknowledged at first contact. Aim: To explore sex- and age-related differences in patient-reported typical and atypical symptoms of stroke. Methods: We used data from a cross-sectional survey at two non-comprehensive stroke units in the Capital Region of Denmark. Patient-reported symptoms, stroke knowledge, and behavioral response were analyzed by Chi-square test or a Fisher’s exact test separated by sex. Multivariable logistic regression adjusted for covariates were used to explore sex- and age-related differences according to each patient-reported typical or atypical symptoms. Results: In total, 479 patients with acute stroke were included (median age 74 years [25th – 757h percentile: 64-80], and 40.1 % were women). Female sex was associated with higher odds of presenting with the atypical symptoms such as loss of consciousness (OR 2.12 [95% CI 1.08-4.18]) and nausea/vomiting (OR 2.33 [95% CI 1.24-4.37]), and lower odds of presenting with lower extremity paresis (OR 0.59 [95% CI 0.39-0.89). With each year of age the odds decreased of presenting with sensory changes (OR 0.95 [95% CI 0.94-0.97]) and upper extremity paresis (OR 0.98 [95% CI 0.96-0.99]) whereas odds of presenting with dysphagia (OR 1.06 [95% CI 1.02-1.11]) increased. Conclusions: Patients of female sex and younger age reported on admission more frequently atypical stroke symptoms. Attention should be drawn to this possible atypical first presentation to facilitate correct identification and early stroke revascularization treatment to improve outcome for both sexes.